1962
DOI: 10.1039/jr9620004540
|View full text |Cite
|
Sign up to set email alerts
|

879. A polarographic investigation into the redox behaviour of quinones: the roles of electron affinity and solvent

Abstract: One-electron reduction potentials, El, of thirty quinones in apmtic conditions have been determined. A comparison with published molecularorbital calculations shows that electron addition takes place to the lowest unoccupied molecular orbital. The El values are linearly related to the electron affinity of the quinones. Intramolecular hydrogen bonding leads to an enhanced electron affinity in some a-hydroxy-quinones and apparently also in an unconjugated hydroxy-quinone. Although some El values for hydroxylic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(142 citation statements)
references
References 0 publications
10
132
0
Order By: Relevance
“…The collected precipitate was washed with water and recrystallized from methanol (MeOH) to yield pure, orange-brown HI (0.78 g): mp 258-62°C (dec.) [lit. (10) 20.16% N. The mass spectrum of the derivative also was consistent with the desired product.…”
mentioning
confidence: 56%
“…The collected precipitate was washed with water and recrystallized from methanol (MeOH) to yield pure, orange-brown HI (0.78 g): mp 258-62°C (dec.) [lit. (10) 20.16% N. The mass spectrum of the derivative also was consistent with the desired product.…”
mentioning
confidence: 56%
“…This type of reaction between semiquinone radicals and H 2 O 2 has been previously proposed by Koppenol and Butler (39), who suggested that if a quinone/ semiquinone couple has a reduction potential of between -330 and +460 mV, it can theoretically bring about a metalindependent Fenton reaction. It was suggested that such reactions are thermodynamically feasible and do not require metal ions for catalysis (39,40), which might be the case in this study, where the reduction potentials of the quinone/semiquinone couples for 2-chloro-, 2,5-dichloro-, tetrafluoro-, tetrabromo-, and tetrachloro-1,4-benzoquinone are -100, +60, +200, +240, and +250 mV, respectively (41). These values are within the suggested range of -330 to +460 mV.…”
Section: Molecular Mechanism Of Metal-independent Production Ofmentioning
confidence: 95%
“…The one-electron reduction potentials of quinone in aprotic solvent, measured polarographically from the half-wave potential (vs. saturated calomel electrode) were 0.54 and 1.23 V (Peover, 1962). The equilibrium constants for hausmannite and manganite (Bolt and Bruggenwert, 1976) The appearance of semiquinone anion radical indicates that the reduction of the hausmannite was a one-electron transfer process.…”
Section: Thermodynamic Studiesmentioning
confidence: 99%